Worker Protection, Japanese Style : Occupational Safety and Health in the Auto Industry - Lewchuk, Wayne (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Worker Protection, Japanese Style : Occupational Safety and Health in the Auto Industry," by Richard E. Wokutch.
Keywords: AUTOMOBILE industry; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor unions; Occupational safety; Safety measures; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z